Numerical investigations on resistive cooling of trapped highly charged ions - Maero, Giancarlo; Kluge, Heinz-Jürgen (Applied physics. B, Lasers and optics, 2012)
The investigation of simple atomic systems in extreme electromagnetic fields with highest precision demands intense beams of heavy and highly charged ions to be decelerated and cooled to extremely low energies for long-time observation. Resistive cooling, i.e., the electronic dissipation of energy of a stored ion cloud on an external impedance, seems to be a good candidate for in-trap cooling of highly charged ions and has been chosen for the upcoming HITRAP (Highly charged Ion TRAP) facility at GSI, Darmstadt. Nevertheless, resistive cooling of large ensembles of ions confined in a Penning trap has never been thoroughly studied until now and the understanding of this highly nonlinear phenomenon is far from complete. Through the use of systematic simulations we give a proof of the feasibility of resistive cooling of large numbers of highly charged ions as well as the interpretation of some specific features observed experimentally.